1990
DOI: 10.1007/bf02764284
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal silicone oil injection: complications and treatment of 415 consecutive patients

Abstract: Silicone oil injection in conjunction with pars plana vitrectomy was carried out by five surgeons in 415 consecutive patients using the same surgical equipment, the same surgical techniques and the same highly purified silicone oil (viscosity, 5000 mPa.s). Indications for silicone oil injection after vitrectomy included advanced stages of proliferative vitreoretinopathy following rhegmatogenous retinal detachment (49%), severe proliferative diabetic retinopathy (38%), and proliferative vitreoretinopathy follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
95
1
11

Year Published

1992
1992
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(110 citation statements)
references
References 31 publications
3
95
1
11
Order By: Relevance
“…In our study, total anatomic success at the last follow-up visit was achieved in 25 of the 27 patients (92.5%), which is similar to the previous results reported for the treatment of severe RD with both standard silicone oil [8,12,16,19] and the heavy silicone oils Oxane Hd® and Densiron 68® [9,18,21,22,29,30].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, total anatomic success at the last follow-up visit was achieved in 25 of the 27 patients (92.5%), which is similar to the previous results reported for the treatment of severe RD with both standard silicone oil [8,12,16,19] and the heavy silicone oils Oxane Hd® and Densiron 68® [9,18,21,22,29,30].…”
Section: Discussionsupporting
confidence: 91%
“…Vitreoretinal proliferation occurs more frequently in the inferior quadrants, as cells gather in the watery space between the retina and the oil bubble due to the gravity. [5][6][7][8][9] Therefore, there may be a specific role for tamponade agents with a specific gravity higher than that of water. Several heavier-than-water fluorinated silicone oils have been evaluated for intraocular use.…”
Section: Introductionmentioning
confidence: 99%
“…This assumption seems to be supported by clinical studies on the complications of vitrectomy and the use of intravitreal substitutes, in which the formation of a cataract is a common postoperative finding [8][9][10][11]. In an animal experiment performed by Repka et al [12], cystic macular lesions were observed after intravitreal injection of CBF s gas.…”
Section: Discussionmentioning
confidence: 48%